Efektivitas Tugas Video dalam Pembelajaran Bahasa Inggris: Studi Kasus Mahasiswa Manajemen Universitas BSI - Mursyid Kasmir Naserly (Journal on Education, 2024)
This study explores the effectiveness of video assignments as a tool for learning English, particularly in the English for Business course. Using a qualitative descriptive approach, this research focuses on the experiences and perceptions of 20 management students from Universitas BSI who completed video assignments on sales and marketing topics. The findings reveal that video assignments significantly enhance students' language skills and confidence. Students faced various challenges, including technical issues and language barriers, but these were overcome through practice and resource utilization. The study highlights the importance of guidance and feedback from lecturers to support students in overcoming these challenges. Overall, video assignments are deemed an effective method for improving students' English language skills.